Catalytic CO2 Methanation: Providing Optimal Test Conditions for Kinetic Investigations. Issue 5 (9th March 2023) - Failing, Luisa; Strucks, Peter; Kaluza, Stefan
Abstract: In the context of using renewable energies and recycling climate‐changing gases, methanation of CO2 provides one possibility. However, volatile availability of renewable energies for hydrogen production and fluctuating CO2 streams from different sources lead to enhanced demand in investigating the influence of dynamic process operation on the catalyst performance, including detailed kinetic characterization. Reliable kinetic measurements require isothermal temperature control and absence of macrokinetic diffusion limitations. Both were investigated in this work while the determination of steady‐state kinetic parameters is part of ongoing studies. Furthermore, a detailed analysis with respect to the long‐term‐stability of the nickel‐based catalyst was performed. Abstract : Today, the catalytic methanation of CO2 enables chemical energy storage in a cycle (Power‐to‐Gas). Coupling of methanation to decentralized CO2 sources results in the need for dynamic process operation. For reliable kinetic measurements using a nickel‐based catalyst, isothermal temperature control and the absence of macrokinetic diffusion limitations as well as the long‐term stability of the catalyst were investigated.